Implementasi Framework Laravel Pada Aplikasi Pengolah Nilai Akademik Berbasis Web - Sari Susanti; Erfian Junianto; Rizal Rachman (Jurnal Informatika, 2017)
AbstractStudent Grades is one of the important things in the school. Based on the regulation of education and culture minister of the Republic of Indonesia number 66 of 2013 on standard educational assessment mentions that the results of the assessment by educators and educational units reported in terms of value and description of the achievement of competence to parents and the government. Values and descriptions of student competence achievement processed manually so it takes a long time in the process. That requires an application that can process value. Making a web application processing of the students is one of the solutions in the processing of value. The web application processing student value is made using the waterfall model that includes: analysis, design, coding and testing. on this website are processed according to the rules curriculum assessment in 2013 which has three criteria: the value of knowledge, skills and value attitudes. The end result of these values is processed into value of report cards. Making the web using PHP programming language and MySQL database storage. From the results of research conducted conclusion that the Web Application Processing Value is an application that helps the processing of value for homeroom and make it easier for the students see the value. Keywords: Grades Processing, Web Application, Framework Laravel, Website, Curriculum in 2013. Abstrak Nilai merupakan salah satu hal penting di sekolah. berdasarkan peraturan menteri pendidikan dan kebudayaan Republik Indonesia nomor 66 tahun 2013 tentang standar penilaian pendidikan menyebutkan bahwa hasil penilaian oleh pendidik dan satuan pendidikan dilaporkan dalam bentuk nilai dan deskripsi pencapaian kompetensi kepada orang tua dan pemerintah. Nilai dan deskripsi pencapaian kompetensi siswa masih diolah secara manual sehingga membutuhkan waktu lama dalam pengerjaannya. Untuk itu dibutuhkan sebuah aplikasi yang dapat mengolah nilai. Pembuatan aplikasi web pengolahan nilai siswa adalah salah satu solusi untuk mengatasi lambatnya pengolahan nilai. Aplikasi web pengolahan nilai ini dibuat menggunakan model waterfall yang mencakup : analisis, desain, pengkodean dan pengujian. pada website ini penilaian diproses berdasarkan standar kurikulum 2013 yang memiliki tiga kompetensi nilai yaitu pengetahuan, keterampilan dan sikap. Hasil akhir dari ketiga nilai tersebut diproses menjadi nilai rapor. Pembuatan web ini menggunakan bahasa pemrograman PHP dan penyimpanan basis data MySQL. Dari hasil penelitian yang dilakukan diperoleh kesimpulan bahwa Aplikasi Web Pengolahan Nilai merupakan solusi yang membantu proses pengolahan nilai bagi wali kelas dan kemudahan bagi siswa untuk melihat nilainya. Kata Kunci: Pengolahan Nilai, Aplikasi Web, Framework Laravel, Website, Kurikulum 2013.